Effect of Bamboo (Bambusa sp) Shoot Liquid Organic Fertilizer On Growth of Pre-Anthesis Cayenne Pepper (Capsicum frutescens L.) By Hydroponics - Dwijowati Asih Saputri; Marlina Kamelia; Nurhaida Widiani; Ari Hermawan (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2021)
An environmentally friendly agricultural system with organic fertilizer is used to reduce the use of chemical fertilizers, thus producing healthy agricultural products for consumption. Liquid organic fertilizer from bamboo shoots is an alternative substitute for chemical fertilizers in the planting of cayenne pepper (Capsicum frustescens L.) hydroponically. This study aims to determine the effect of bamboo shoot liquid organic fertilizer on hydroponic cayenne pepper pre-antithesis growth. The study was conducted at the Biology Laboratory of UIN Raden Intan Lampung, using a Completely Randomized Design (CRD) with 6 treatments with 3 replications. The treatments included negative control (water), positive control (AB mix), P1 = 10%, P2 = 15%, P3 = 20%, P4 = 25% ml. The parameters include plant height, number of leaves, stem diameter, plant fresh weight. Data were analyzed using One Way Anova (SPSS 17.0), followed by LSD at the 5% level. The results show the effect of treatment on all parameters. Control positive (AB mix) gave the best results on all parameters, then successively treated P4, P3, P2, P1, K0 (negative control). Although not as good as using an AB mix solution, the administration of bamboo shoots POC with a concentration of 25% can support the growth of hydroponic cayenne pre-synthesis.